Half-Brothers in Christ: The Church Missionary Society and the Christians of Kerala, 1813-1840 - Joseph Gerald Howard (SIMON FRASER UNIVERSITY, 2014)
In the 1810s, the Church Missionary Society (CMS) established the College at Cottayam in south India to educate boys intended for the priesthood in the local, indigenous church. While their goal was to help the church, their activities increased British power in the community. The results of CMS involvement included increasing interference of British officials in matters internal to the Malankara Church (e.g., episcopal succession), tacit recognition of the authority of colonial courts to resolve disputes in the church, and the fragmentation of the St. Thomas Christian community. These effects reshaped the church into something more consistent with British Christianity and more subject to British rule.